Guinea pigs - Evans, Mark, 1962- (Boston : Distributed by Houghton Mifflin, 1992)
Offers information for the first-time pet owner on the physical characteristics, selection, care, and feeding of guinea pigs.
Life in the wild -- All color patterns -- Things you will need -- Welcome home -- Friends for your guinea pigs -- Feeding fresh foods -- Cleaning the hutch -- Grooming your guinea pig -- Health care -- Visiting the veterinarian.
Includes index.
Booklist.
Elem. School Library Collection.
School Library Journal.
4.4.
4.4
Keywords: Guinea pigs as pets -- Juvenile literature; Guinea pigs as pets; Guinea pigs; Pets; Guinea pigs; Pets